2018
DOI: 10.1136/tobaccocontrol-2017-053868
|View full text |Cite
|
Sign up to set email alerts
|

UK news media representations of smoking, smoking policies and tobacco bans in prisons

Abstract: BackgroundPrisoner smoking rates remain high, resulting in secondhand smoke exposures for prison staff and non-smoker prisoners. Several jurisdictions have introduced prison smoking bans with little evidence of resulting disorder. Successful implementation of such bans requires staff support. As news media representations of health and other issues shape public views and as prison smoking bans are being introduced in the UK, we conducted content analysis of UK news media to explore representations of smoking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…25,26 These concerns, rather than public health gains, have dominated much media coverage around the introduction of smoke-free prisons. 27…”
Section: Introductionmentioning
confidence: 99%
“…25,26 These concerns, rather than public health gains, have dominated much media coverage around the introduction of smoke-free prisons. 27…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates reports of SFPPs in Australia and the USA, 6 , 17 and contradicts common media portrayals. 18 Finally, our study strengthens understanding of successful factors for creating smokefree prisons by being the first to comprehensively investigate the perspectives of prison staff and PiC across a prison system post-implementation. The findings provide deeper insight into the role of factors such as extensive planning work; comprehensive communication and engagement with stakeholders and supporting PiC to abstain/quit smoking in successfully implementing SFPP (see also 6 , 19 ).…”
Section: Discussionmentioning
confidence: 58%
“…They also suggested strategies to mitigate these challenges. Some reflected media coverage of prison bans elsewhere 24 in expressing worries that a ban may precipitate serious unrest or riots.…”
Section: Discussionmentioning
confidence: 99%
“…23 Given this context, it is perhaps unsurprising that much of the discourse around removing tobacco from prisons has focused on the risk of unrest, at the expense of discussion of potential public health gains. 24 Relatively little research has been published on the process or outcomes of prison smoking 'bans'. The best evidence available in 2015/16, following New Zealand's experience of implementing a comprehensive ban, 25,26 suggested that at least 1 year is needed to prepare for a smoke-free policy in prisons.…”
Section: Legislative and Policy Context Prior To Commencement Of The ...mentioning
confidence: 99%